Practice book 4: phonic reading scheme - Corby, Jill; Dwyer, Derek (Loughborough: Ladybird, 1993)
This activity book is intended for beginner readers and Part of a reading scheme that can be used alongside any other method of learning to read. features Ben and Jenny, two lively six to seven year old . Through their games and activities the reader is transported to a world of make-believe.